Pertangungjawaban Pidana Pemegang Saham pada Tindak Pidana Korporasi dalam Undang-Undang Nomor 1 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana (KUHP) - Rio Fransiscus Girsang; Alvi Syahrin; Edi Yunara; Rosmalinda Rosmalinda (Dinasti Review Publisher, 2024)
Corporations have a strategic role in bringing about change and growth in the world economy. Corporations are second only to the State in increasing economic growth and national development, but there are times when corporations also commit various criminal acts that harm the state and society. The damage to banking that occurred in the past was precisely due to the actions of the controlling shareholders of the banks, through the GMS placing people (minions) as members of the board of directors and commissioners. These people who were given strategic positions by the controlling shareholders were puppets of the controlling shareholders and carried out the policies of the controlling shareholders. The case of Bank Harapan Sentosa (BHS) shows how the shareholders had evil intentions by creating a